Integrating Digital Literacy in English for Specific Purposes (ESP) Instruction Via English for Law e-module - Surani, Dewi; Umalihayati, Umalihayati; Septiyani, Rini Dwi; Holilah, Holilah (Journal of English Teaching and Learning Issues, 2023)
Nowadays, integration of technology through digital literacy in English instruction is demanded highly, but in practice, digital material like electronic modules still lacks investigation, especially in the ESP context. Therefore, this qualitative study tries to describe the digital literacy demand related to the material in ESP teaching and the implementation of digitalized based ESP material to facilitate law students’ digital literacy. 25 law students were involved as participants, with the questionnaires and interviews as the primary data and class observation as the secondary data. The results reveal that ESP language-teaching process demands digitalized material which facilitates the students’ needs in enhancing their English skills by exploring authentic learning sources digitally. The implementation of the English for Law e-module facilitates students’ digital literacy, especially in accessing the digital material in the e-module by 70% of the whole participants, 57,7 % of students use their digital literacy for finishing the lectures assignment, and 74% of students able to overcome their digital obstacle independently. The finding recommends the utilization of digitalized material based on e-module to cultivate the students’ digital literacy in ESP instruction.